Chakri Maha Prasat: A Colonial Discourse in Siamese Architecture - Koompong Noobanjong (My University, 2006)
Modernity is a creation of the West. In a non-Western context, it normally reflects a direct interventionof the Western powers by means of colonization. However, the Siamese, known today as the people of Thailand,have argued that they are an exception to such an occurrence.
The shift toward Western culture and Modernity is evident in the production of Thai cultural artifacts,notably its art and architecture throughout the 19th and 20th centuries. Many works have been the results of hybriddesigns—the syntheses between European and Siamese artistic styles, either in painting, sculpture, costume,music, literature, performing art, cuisine, or architecture. One of the best known examples is the Chakri MahaPrasat. Situated at the central location in the Grand Palace or Praborommaharajawung in Bangkok, this thronehall holds more importance than simply evidence of stylistic changes; it is in essence a manifestation of social,political, and cultural awareness, as well as bearers of national identity.
This research illustrates how various architectural ideas have contributed to the physical design andspatial configuration of places associated with negotiation and allocation of political power in 19th century Siam,such as the Chakri Maha Prasat. It also examines the Siamese’s resistance and reconciliation to process ofcolonization.
Keywords: Sculpture; Southeast Asian Sociopolitical Studies